Exploration of Secondary Metabolite Production Potential in Actinobacteria Isolated From Kandelia candel Mangrove Plant - Hu, Dini; Lee, Simon Ming-Yuen; Li, Kai; Mok, Kai Meng (Frontiers in Marine Science, 2022)
Mangroves are extreme inter-tidal environments containing rich microbial communities. Actinobacteria from mangroves have an unprecedented ability to biosynthesize secondary metabolites. Therefore, the secondary metabolite production potential of actinobacteria sourced from mangroves warrants further exploration to determine whether they offer new sources of natural products. For this purpose, we selected a strain of Mycobacterium saopaulense (Actinobacteria phylum) from the mangroves in Macau for whole genome sequencing and tandem mass spectrometry analysis. The results showed that the 5,376,881-bp genome from this strain contains 5,391 protein-coding genes and a coding density of 90.53%. The main participating KEGG pathway was “Metabolism”. Altogether, the 81 gene clusters identified in its genome were associated with the production of 23 secondary metabolites. Sixteen of them were classified as antibiotics and three of them as bioactive compounds. Furthermore, two of the predicted secondary metabolites from the fermentation process were clavulanic acid and streptomycin. Both of these antibiotics were initially found to be produced by the M. saopaulense strain. This study shows that mangrove-derived actinobacteria have a large number of biosynthetic pathways with the potential to produce a range of biologically active secondary metabolites.